Bevacizumab (BVZ)‐associated toxicities in children with recurrent central nervous system tumors treated with BVZ and irinotecan (CPT‐11). Issue 23 (19th September 2013) - Fangusaro, Jason; Gururangan, Sridharan; Poussaint, Tina Young; McLendon, Roger E.; Onar‐Thomas, Arzu; Warren, Katherine E.; Wu, Shengjie; Packer, Roger J.; Banerjee, Anu; Gilbertson, Richard J.; Jakacki, Regina; Gajjar, Amar; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND The incidence and spectrum of acute toxicities related to the use of bevacizumab (BVZ)‐containing regimens in children are largely unknown. This report describes the adverse events in a recently completed large phase 2 trial of BVZ plus irinotecan (CPT‐11) in children with recurrent central nervous system tumors. METHODS Pediatric Brain Tumor Consortium trial‐022 evaluated the efficacy and toxicity of BVZ (10 mg/kg administered intravenously) as a single agent for 2 doses given 2 weeks apart and then combined with CPT‐11 every 2 weeks (1 course = 4 weeks) in children with recurrent central nervous system tumors. Children were treated until they experienced progressive disease, unacceptable toxicity or completed up to a maximum of 2 years of therapy. Toxicities were graded according to the National Cancer Institute Common Terminology Criteria for Adverse Events, version 3.0. Patients who received at least 1 dose of BVZ were included for toxicity assessment. RESULTS Between October 2006 and June 2010, 92 patients evaluable for toxicity were enrolled and received 687 treatment courses. The most common toxicities attributable to BVZ included grade I‐III hypertension (38% of patients), grade I‐III fatigue (30%), grade I‐II epistaxis (24%), and grade I‐IV proteinuria (22%). Twenty‐two patients (24%) stopped therapy due to toxicity. CONCLUSIONS The combination of BVZ and CPT‐11 was fairly well‐tolerated, and most severe BVZ‐related toxicities were rare, self‐limiting, and manageable. Cancer 2013;119:4180–4187. ©2013 American Cancer Society.